AKTIVITAS FISIK DAN KONSUMSI KEDELAI PADA REMAJA PUTRI YANG MENGALAMI PREMENSTRUAL SYNDROME DI SMKN 10 SURABAYA - Eva Flourentina Kusumawardani; Annis Catur Adi (Media Gizi Indonesia, 2017)
Premenstrual Syndrome (PMS) is a group of symptoms that occur 1–2 weeks before menstruation period and cause  lower concentration and absents at school. The aim of this study was to describe the association between physical activity and soy dietary intake among adolescent girls who experienced PMS at SMKN 10 Surabaya. This studywas an observational analytic with cross sectional design. Samples were taken as many as 59 students aged 14–17 years old using systematic random sampling. Data were analyzed using chi-square. The study showed that physical activity level of respondents were light (88.1%). 10.2% respondents doing walk and bicycle > 7x in the past 7 days.Soy comsumption level of respondents were moderate (17.22–28.38 portion per month). Tofu (69.5 %) and tempeh (66.1%) were processed product of soybean that frequently consumed by respondents as much as 75 g. Adolescent girls had low physical symptoms of PMS (71.2%). The frequent symptoms were fatigue (25.4%), paintful and tenderbreast (35.6%). There was a signiﬁ cant relationship between PMS with physical activity with PMS (p = 0.011) and soy consumption (p = 0.000). High soy consumption, regular and moderate physical activity can help reduce unfavorable PMS symptoms.